2016
DOI: 10.1097/mou.0000000000000240
|View full text |Cite
|
Sign up to set email alerts
|

New technology in ureteroscopy and percutaneous nephrolithotomy

Abstract: Based on recent technical developments, percutaneous nephrolithotomy and particularly flexible ureteroscopy will further gain preference in management of urolithiasis compared to ESWL. Endourology may offer a higher rate of primary success with minimal side-effects which could weigh out the slightly higher degree of invasiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(53 citation statements)
references
References 45 publications
1
47
0
3
Order By: Relevance
“…Only two cases required secondary conventional fURS, and ergonomic questionnaire scores significantly favored the robotic platform over conventional URS in seven queried surgeons (P < 0.01). Data from 90 cases performed by three surgeons in Heilbronn, Germany, reproduced these initial results and further demonstrated that fragment extraction was possible [38]. These results support that the robotic platform may be a safe and effective alternative method to conventional URS with potential advantages for both the patient and the surgeon.…”
Section: New Methods For Ureteroscopysupporting
confidence: 78%
See 1 more Smart Citation
“…Only two cases required secondary conventional fURS, and ergonomic questionnaire scores significantly favored the robotic platform over conventional URS in seven queried surgeons (P < 0.01). Data from 90 cases performed by three surgeons in Heilbronn, Germany, reproduced these initial results and further demonstrated that fragment extraction was possible [38]. These results support that the robotic platform may be a safe and effective alternative method to conventional URS with potential advantages for both the patient and the surgeon.…”
Section: New Methods For Ureteroscopysupporting
confidence: 78%
“…Clear Guide One (Clear Guide Medical, Baltimore, MD, USA) is an optical tracking system that mounts on an ultrasound probe and provides real-time tracking for needles and instruments [38]. The Clear Guide Synergy adds CT image fusion capability to this technology.…”
Section: New Methods For Percutaneous Nephrolithotomymentioning
confidence: 99%
“…Yapılan erken dönem çalışmalarda Robotik fleksibl URS'nin oldukça ergonomik olduğu ve başarılı sonuçlar elde edildiği bildirilmiştir (33,41,42). Biz de kliniğimizde toplam 11 hastada robotik fleksibl URS'yi deneme şansı bulduk (Resim 8).…”
Section: Resim 7: Robot Yardımlı Fleksibl Urs (41)unclassified
“…The perfect puncture could be a scanner guided puncture. There are several publications explaining that possibility, but of course this is not useful in daily practice and the radiation exposure of the patient is another important issue [24]. Dybowski et al [25] recommend to avoid or prevent complications by the creation of centers of excellence (stone centers) and to improve teaching techniques by using virtual reality technologies and simulators.…”
Section: Figure 2 the Thin Needle Informs Us If The Calyx Is Deep Ormentioning
confidence: 99%